2006
DOI: 10.1111/j.1460-9568.2006.04631.x
|View full text |Cite
|
Sign up to set email alerts
|

CXCL10‐induced cell death in neurons: role of calcium dysregulation

Abstract: Chemokines play a key role in the regulation of central nervous system disease. CXCL10 over-expression has been observed in several neurodegenerative diseases, including multiple sclerosis, Alzheimer's disease and HIV-associated dementia. More recent studies by others and us have shown that CXCL10 elicits apoptosis in fetal neurons. The mechanism of CXCL10-mediated neurotoxicity, however, remains unclear. In this study, we provide evidence for the direct role of Ca(2+) dysregulation in CXCL10-mediated apoptosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
133
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 152 publications
(140 citation statements)
references
References 47 publications
6
133
1
Order By: Relevance
“…Activation of caspase 3 and 9 was shown to play a crucial role in CXCL10-dependent neuronal apoptosis observed in human fetal neuronal cell cultures (Sui et al, 2006). In our studies using rat hippocampus obtained from embryos at an older age (equivalent to third trimester human hippocampus) and chronic exposure to higher concentrations of CXCL10 for 9 days there was no evidence of toxicity by CXCL10.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…Activation of caspase 3 and 9 was shown to play a crucial role in CXCL10-dependent neuronal apoptosis observed in human fetal neuronal cell cultures (Sui et al, 2006). In our studies using rat hippocampus obtained from embryos at an older age (equivalent to third trimester human hippocampus) and chronic exposure to higher concentrations of CXCL10 for 9 days there was no evidence of toxicity by CXCL10.…”
Section: Discussionmentioning
confidence: 47%
“…A recent study showed that exposure to low concentrations of exogenous CXCL10 (10-100 ng/ml) for 18 h has pro-apoptotic effects on human fetal neuronal cell cultures (Sui et al, 2006). Activation of caspase 3 and 9 was shown to play a crucial role in CXCL10-dependent neuronal apoptosis observed in human fetal neuronal cell cultures (Sui et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although underlying mechanisms are unclear, similar effects of CXCL10 are observed in brain neuronal culture and endothelial cells in a mechanism involving CXCR3-mediated caspase 3 activation. 64,65 Leukocyte recruitment is a response to tissue injury and infection and contributes to the development and resolution of many infectious diseases. Leukocyte imaging has been used for three decades as the gold standard for the imaging and diagnosis of most infections in the immunocompetent population.…”
Section: Discussionmentioning
confidence: 99%
“…The chemokines CXCL10, CXCL12, and CCL2 have drawn substantial attention because of their pluripotent effects, including chemotaxis and neurotoxicity together with their cognate receptors' important downstream effects (6). For example, CXCL10, also termed interferon-g inducible protein-10, is upregulated in HIV-and SIVinfected brains (7), whereas its receptor CXCR3 appears to mediate neurotoxicity that depends on the individual isoform (8,9). Hence, this group of soluble molecules represents important pathogenic factors in neurovirulence as proposed for other nervous system infections, perhaps by multiple mechanisms including chemotaxis of circulating leukocytes and direct neurotoxic actions.…”
mentioning
confidence: 99%